2005
DOI: 10.1139/b04-171
|View full text |Cite
|
Sign up to set email alerts
|

Microfungal endophytes in roots

Abstract: A wide range of ascomycetous microfungi inhabits roots without forming the anatomical features typical of mycorrhizas or causing overt signs of pathogenesis. The most-studied taxa have darkly pigmented hyphal walls and are referred to as "dark septate endophytes" (DSE). We provide a dichotomous key and annotated descriptions for a cross-section of the most common dark septate endophytes. The term DSE is sometimes used to imply taxonomic and physiological similarity even though a diverse range of root endophyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
132
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(147 citation statements)
references
References 90 publications
3
132
5
Order By: Relevance
“…3). These results suggest that DSE are probably weak parasites supporting some earlier conclusions (Addy et al 2005, Alberton et al 2010, although some strains may behave as mutualists. However, a recent meta-analysis (Newsham 2011) suggested that the DSE symbioses tended to be positive, though mainly so if nitrogen was supplied in organic forms.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…3). These results suggest that DSE are probably weak parasites supporting some earlier conclusions (Addy et al 2005, Alberton et al 2010, although some strains may behave as mutualists. However, a recent meta-analysis (Newsham 2011) suggested that the DSE symbioses tended to be positive, though mainly so if nitrogen was supplied in organic forms.…”
Section: Discussionsupporting
confidence: 89%
“…Although many DSE fungi form similar morphological structures in the host roots (Jumpponen & Trappe 1998, Rodriguez et al 2009), they are taxonomically unrelated, vary in ecological or physiological functions and lead to variable host responses (Addy, Piercey & Currah 2005, Alberton, Kuyper & Summerbell 2010, Newsham 2011, Tellenbach, Grünig & Sieber 2011, Knapp, Pintye & Kovacs 2012. Our earlier studies in the tallgrass prairie concluded that while grasses overall tend to be colonized to a greater extent and respond more positively to DSE colonization, forbs also range from increased to no response to decreased biomass accumulation in their response to DSE fungi (Mandyam, Fox & Jumpponen 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these morphological characters, it is unlikely that the fossils share an affinity with the basidiomycetous Rhizoctonialike soil pathogens, but hyphal features alone do not permit us to more precisely identify them, especially because monilioid growth is common to many fungi that colonize vascular plants, including both plant pathogens and endophytes (Melin 1923, Parmeter and Whitney 1970, Currah et al 1988. Unambiguous identification of sterile mycelia in living fungi depends upon observing their association with conidial or sexual phases, characterizing substrate utilization, or molecular taxonomy (Addy et al 2005, García et al 2006. …”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that P. fortinii exhibits versatile capacities of promoting elemental nitrogen (N) and phosphorus (P) absorption by host plants [25] and synthesizing glucose [26] by co-existing with host roots. Further, P. fortinii have also been shown to aid the enhancement of disease resistance in hosts, controlling Verticillium yellows in Chinese cabbage [27], the capacity to produce chemicals such as hydroxamate siderophore [28] and other enzymes in improving host resistance and absorption of nutrients, for example, production of extracellular aryl sulfatase to decompose aryl sulphates [29]. All of these abilities, along with its ability to produce SAL and TYR, suggest that P. fortinii plays a key role in symbiosis with host plants.…”
Section: Discussionmentioning
confidence: 99%